Inhibition of Drp1 by Mdivi-1 attenuates cerebral ischemic injury via inhibition of the mitochondria-dependent apoptotic pathway after cardiac arrest. (17th December 2015) - Li, Y.; Wang, P.; Wei, J.; Fan, R.; Zuo, Y.; Shi, M.; Wu, H.; Zhou, M.; Lin, J.; Wu, M.; Fang, X.; Huang, Z.
Highlights: Cardiac arrest leads to Drp1 activation. Inhibition of Drp1 by Mdivi-1 attenuates cardiac arrest-induced cerebral ischemic injury. Mdivi-1 is administrated after ROSC, a clinically relevant intervention period. The neuroprotective effect of Mdivi-1 may be dose-dependent. The mechanisms involve CytC and AIF-dependent mitochondrial apoptosis pathway. Abstract: Mitochondrial fission is predominantly controlled by the activity of dynamin-related protein1 (Drp1), which has been reported to be involved in mitochondria apoptosis pathways. However, the role of Drp1 in a rat model of cardiac arrest remains unknown. In this study, we found that activation of Drp1 in the mitochondria was increased after cardiac arrest and inhibition of Drp1 by 1.2 mg/kg of mitochondrial division inhibitor-1 (Mdivi-1) administration after the restoration of spontaneous circulation (ROSC) significantly protected against cerebral ischemic injury, shown by the increased 72-h survival rate and improved neurological function. Moreover, the increase of the vital neuron and the reduction of cytochrome c (CytC) release, apoptosis-inducing factor (AIF) translocation and caspase-3 activation in the brain indicate that this protection might result from the suppression of neuron apoptosis. Altogether, these results indicated that Drp1 is activated after cardiac arrest and the inhibition of Drp1 is protective against cerebral ischemic injury in a rat of cardiac arrest model via inhibition of the mitochondrial apoptosis pathway.